First identification report for amino acid composition of red algae Gracilaria spp. obtained from Central Java, Indonesia - Klara Kharisma Bunga Chandra; Tri Rini Nuringtyas; Tri Joko Raharjo (BioTechnologia)
Gracilaria is a genus of red algae found mainly in Asia. Various species of Gracilaria are distributed throughout Indonesia’s marine waters, especially in coastal areas, and are cultivated for research and economic purposes. Gracilaria mainly consists of polysaccharides and pigments, which have hindered protein identification. The unique protein expressions have never been analyzed using a proteomic approach, and no reports are available on Gracilaria spp. amino acid sequences in Central Java. Based on this background, we aimed to explore Gracilaria protein characterization using unique peptide sequence analysis via LC-HRMS. The usage of liquid chromatography coupled with high-resolution mass spectrometry (LC-HRMS) has been growing in biomedical and environmental sciences, offering high accuracy in protein detection. We followed the LC-HRMS standard protocol with an optimized precipitation procedure. TCA/acetone precipitation was used for protein purification, after which the precipitate was subjected to protein digestion to obtain small peptide fractions. Protein analysis results are presented as protein concentrations, molecular models, and peptide sequences. This experiment identified four sequences derived from the Rhodophyta database: TKKILDK (845.5455 Da), TVKSLLTK (889.5717 Da), ILVKTLK (814.5761 Da), and TGcGRSKR (921,4683 Da). This study reveals peptide sequences for Gracilaria spp., showing similarities with other red algae species, along with the functions of the peptide sequences. Furthermore, amino acid models of secondary structures were provided to support our findings.